The voiding of being : the doing and undoing of metaphysics in modernity - Desmond, William, 1951- (Studies in philosophy and the history of philosophy, 2020)
"The author amplifies important themes in the unfolding of modern metaphysics, exploring diverse aspects of current skepticism and offering a defense in terms of his metaxological metaphysics. Along the way he engages both the long tradition and more modern writers, such as Heidegger and Marion"--